A Different Tenor: Glimpses and Critical Reflections: Kawuki Mukasa's Human Sexuality and Religion: Reframing the Problem - Galabuzi, Grace-Edward (Toronto journal of theology, 2008)
Different from the tenor of academic essays, the three expositions that follow offer glimpses of and reflections on "a book that stirs ideas about how the relationship between culture and religion shapes our identities, our understanding of the nature of truth and our interpersonal relationships on matters of sexuality. Discussants were invited to submit in writing what they presented at the launch of the book. Originally four, two discussants were scholars outside the study of religion and theology, one taking a Freudian perspective. Missing here only because of the time constraints of the Journal, that perspective is mentioned to suggest the rich interdisciplinary context in which the exchanges occurred at the book launch. Mukasa holds a doctorate degree from the University of st. Michael's College, Toronto. He is the author of Belonging: Constructing a Canadian Theology of Inclusion, Sojourner and In God's Presence. He currently holds the position of Coordinator for Dialogue in Ethics and Interfaith Relations for the Anglican Church of Canada.